Clinical Challenges in Maintenance Electroconvulsive Therapy for Older Patients With Medical Comorbidity. Issue 1 (March 2016) - Sutor, Bruce; Rasmussen, Keith G.
Abstract : Abstract: As patients receiving maintenance electroconvulsive therapy (MECT) age, many will acquire medical illnesses that may complicate their course of ECT and the treatment of their underlying psychiatric conditions. In this study, we present 7 cases of patients receiving MECT whose medical illnesses resulted in clinical reassessment of whether or not MECT should be continued. We discuss clinical implications and considerations for treating medically ill patients with MECT.